Role of Green Finance in Achieving Green Industrialization for Viksit Bharat by 2047 - Perwez, Md Sohail; Ahmad, Ruksar (International Journal of Environmental, Sustainability, and Social Science, 2026)
India’s Viksit Bharat vision by 2047 prioritizes sustainable industrialization, necessitating a shift from fossil-fuel reliance to low-carbon models, with green finance as a cornerstone. This study investigates how green bonds, ESG investments, blended finance, carbon credits, and green banking can fund renewable energy, electric mobility, battery manufacturing, and circular economy initiatives for MSMEs, aligning with SDGs 7, 9, and 13 and Panchamrit climate targets. Using qualitative secondary data analysis from government reports (MNRE, RBI, MoEFCC), international sources (IEA, Statista), and academic literature, it employs descriptive statistics and trend analysis to evaluate progress from 2014 to 2025, noting renewable capacity growth from 35.8 GW to 171.6 GW, an 800-fold EV sales surge, and waste processing rising to 72%. Policy interventions like PLI schemes and sovereign green bonds have reduced import dependence, yet challenges, 66% private sector mitigation finance, 77% RPO compliance, and 1.18% FDI share, persist. Recommendations include strengthening green credit markets via ESG mandates and municipal bonds, expanding public-private partnerships through PLI and sovereign funds, and enhancing MSME literacy to mobilize INR 4.5 lakh crore and cut 155 MtCO₂e by 2030. These strategies will bridge the 10.1 trillion investment gap, ensuring a resilient, net-zero future.